THE INFLUENCE OF AGILITY INDICATORS ON FORMATION OF VOCATIONAL READINESS IN LAW ENFORCEMENT OFFICERS - Andres, Andrii; Kryzhanovskyj, Valerii; Krasovska, Inesa; Bodnarchuk, Olena; Khanikiants, Olena; Mandiuk, Andrii; Rymar, Olha; Solovey, Alla; Sorokolit, Nataliya; Stefanyshyn, Markiian; Yaroshyk, Marta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The experience of warfare in Ukraine proves the importance of increasing the degree of psychophysical readiness in law enforcement officers. The aim - to determine the significance of the main components of physical readiness of law enforcement officers for productive work performing. Material and methods: Servicemen (n=368) of the National Guard of Ukraine were interviewed. Spearman's rank correlation analysis of indicators` interrelation was carried out. The opinions of experts and beginners reliably differed on a number of indicators. Coordination of movements was significantly correlated with relatively the largest number of indicators of physical readiness, as well as psychological performance of servicemen. It has been established that agility is related to concentration, endurance, span and switching of attention. Conclusions: For the successful professional growth of the students of educational institutions of the National Guard of Ukraine, it is necessary to develop their agility, and especially coordination of movements. It is associated with improving the speed and strength of the officers of the National Guard of Ukraine, as well as attention and logical thinking.